2023
DOI: 10.1177/15593258221150704
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Anticancer Effects of p-Coumaric Acid: Focus on Colorectal Cancer

Abstract: Colorectal cancer is considered the second most deadly cancer in the world. Studies have indicated that diet can prevent the risk of developing colorectal cancer. Recently, there has been an increasing interest in polyphenols due to their plausible effect on cancer prevention and treatment. p-Coumaric acid ( p-CouA), a phenolic compound, is a cinnamic acid derivative found in several fruits, vegetables, and herbs. A growing body of evidence suggests that p-CouA may be an effective agent for preventing and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…As examples, quercetin dirhamnoside has been reported to have cytotoxic activity on HeLa cervical cancer cells (Herni Kusriani et al, 2021). Coumaric acid exhibited antitumor effects on melanoma (A375 and B16 cells) (Hu et al, 2020) and colorectal cancer cells (Tehami et al, 2023). Kaempferol rhamnoside has been shown to inhibit MCF-7 breast cancer cell proliferation through the activation of the caspase cascade pathway (Diantini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, quercetin dirhamnoside has been reported to have cytotoxic activity on HeLa cervical cancer cells (Herni Kusriani et al, 2021). Coumaric acid exhibited antitumor effects on melanoma (A375 and B16 cells) (Hu et al, 2020) and colorectal cancer cells (Tehami et al, 2023). Kaempferol rhamnoside has been shown to inhibit MCF-7 breast cancer cell proliferation through the activation of the caspase cascade pathway (Diantini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that m- and p- coumaric acid has a role in anti-oxidant ability [ 88 ]. Several investigations have demonstrated that p-coumaric acid possesses anti-cancer capabilities whereas the potential anti-cancer effects of m-coumaric acid remain uncertain [ 89 ]. Our study provides for the first time evidence of potential compounds with anti-cancer properties derived from the flower of Shorea roxburghii .…”
Section: Discussionmentioning
confidence: 99%
“…Also, apigenin derivatives have been known to induce cell death and cell cycle arrest [ 49 ]. Coumaric acid is known to have a similar effect, but it has targeted mitochondrial-related apoptosis, downregulated specific cyclin-dependent kinases, and decreased the expression of specific oncogenes [ 50 , 51 ]. Perillaldehyde has been shown to reduce bone metastasis of PC-3 prostate cancer cells with repression of the nuclear factor-κB (NF-κB) pathway and receptor activator of NF-κB ligand (RANKL) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%